2016
DOI: 10.5530/ijper.50.4.15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant, Toxicological and wound healing Properties of Hibiscus rosa-sinensis L. (Malvaceae) ethanolic leaves extract on different Experimental animal models

Abstract: Objective: The present research article was conducted to study the toxicity profile, antioxidant potential and wound healing activity of ethanolic leaves extract of Hibiscus rosa-sinensis L. (ELEHR). Materials and Methods: In-vitro antioxidant properties were assessed using DPPH radical scavenging activity, Nitric oxide scavenging activity, and superoxide radical scavenging activity. Acute toxicity was performed to study the general behavioural pattern of mice and sub-acute toxicity studies were performed to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Bright field images of stained cultures indicated that fibroblasts treated with GG deposited more collagen than control fibroblasts, with dense bundles of collagen apparent at 48 h in the GG-treated cultures (Fig. 3), Similar deposition of collagen was observed in a wound healing study using type-2 diabetic rats treated with a crude methanolic extract, containing polysaccharides, from the Malvaceae plant, Sida cordifolia Linn (Pawar et al, 2016) and is also consistent with in vivo results using Hibiscus rosa-sinensis Linn where extracts have been reported to positively influence mechanisms such as fibroblast migration and collagen synthesis at a wound site (Shivananda Nayak et al, 2007, Bhaskar and Nithya, 2012, Mondal et al, 2016. Conversely, staining of cells treated with GGDS and LB indicated that the levels of collagen deposition were similar to that of the control at both 24 and 48 h post-treatment.…”
Section: Histological Stainingsupporting
confidence: 86%
“…Bright field images of stained cultures indicated that fibroblasts treated with GG deposited more collagen than control fibroblasts, with dense bundles of collagen apparent at 48 h in the GG-treated cultures (Fig. 3), Similar deposition of collagen was observed in a wound healing study using type-2 diabetic rats treated with a crude methanolic extract, containing polysaccharides, from the Malvaceae plant, Sida cordifolia Linn (Pawar et al, 2016) and is also consistent with in vivo results using Hibiscus rosa-sinensis Linn where extracts have been reported to positively influence mechanisms such as fibroblast migration and collagen synthesis at a wound site (Shivananda Nayak et al, 2007, Bhaskar and Nithya, 2012, Mondal et al, 2016. Conversely, staining of cells treated with GGDS and LB indicated that the levels of collagen deposition were similar to that of the control at both 24 and 48 h post-treatment.…”
Section: Histological Stainingsupporting
confidence: 86%
“…21,22 Free radical formation has been reported to be a direct consequence of hyperglycemia. 23 Expression of antioxidant enzymes such as superoxide dismutase, glutathione peroxidase and catalase are known to be in the lowest level in pancreatic islet cells compared to other tissues such as the liver, kidney and adipose tissue.…”
mentioning
confidence: 99%
“…Histological observation of excised wound revealed restoration of normal architecture of the skin. In dead space wound, the extract increased superoxide dismutase (SOD) and catalase (CAT) activity, the weight of granulation tissue and hydroxyproline content (Mondal et al, 2016).…”
Section: Hibiscus Rosa-sinensismentioning
confidence: 99%